THE PATHOGENESIS OF URINARY DISORDERS AND ERECTION IN PATIENTS WITH CEREBROVASCULAR DISEASES - P. G. Shvarts; V. V. Dutov; A. S. Kadykov; S. V. Sheldeshev; A. V. Bershadsky (Вестник урологии, 2016)
The paper describes the main pathogenetic mechanisms of forming persistent neurogenic voiding and sexual function in patients with acute and chronic cerebrovascular disease. Neuroanatomy and neurophysiology described urination and sexual function in normal and vascular disease of the brain. Possibilities different centers urination brain to reorganize functions by associative or contralateral areas of innervation. The role of lower urinary tract symptoms and sexual disorders in the diagnosis level and nature of damage to the central nervous system. Revealed the most important clinical and pathogenetic correlation between urinary and reproductive disorders, the most common in acute and chronic ischemia centers urination and sexual function. The possible common ways of pharmacological correction of functional disorders.